Extant primitively segmented spiders have recently diversified from an ancient lineage - Xu, X.; Liu, F.; Cheng, R.C.; Chen, J.; Xu, X.; Zhang, Z.; Ono, H.; Pham, D.S.; Norma-Rashid, Y.; Arnedo, M.A.; Kuntner, M.; Li, D. (Royal Society of London, 2015)
Living fossils are lineages that have retained plesiomorphic traits through long time periods. It is expected that such lineages have both originated and diversified long ago. Such expectations have recently been challenged in some textbook examples of living fossils, notably in extant cycads and coelacanths. Using a phylogenetic approach, we tested the patterns of the origin and diversification of liphistiid spiders, a clade of spiders considered to be living fossils due to their retention of arachnid plesiomorphies and their exclusive grouping in Mesothelae, an ancient clade sister to all modern spiders. Facilitated by original sampling throughout their Asian range, we here provide the phylogenetic framework necessary for reconstructing liphistiid biogeographic history. All phylogenetic analyses support the monophyly of Liphistiidae and of eight genera. As the fossil evidence supports a Carboniferous Euramerican origin of Mesothelae, our dating analyses postulate a long eastward over-land dispersal towards the Asian origin of Liphistiidae during the Palaeogene (39–58 Ma). Contrary to expectations, diversification within extant liphistiid genera is relatively recent, in the Neogene and Late Palaeogene (4–24Ma). While no over-water dispersal events are needed to explain their evolutionary history, the history of liphistiid spiders has the potential to play prominently in vicariant biogeographic studies.